Sacred tradition in the New Testament : tracing Old Testament themes in the Gospels and Epistles - Porter, Stanley E., 1956- (Grand Rapids, MI : Baker Academic, a division of Baker Publishing Group, 2016)
Leading biblical scholar Stanley Porter critiques the state of research regarding the New Testament's use of the Old Testament and sacred traditions. He provides needed orientation for readers interested in New Testament references to themes such as "son of man" and "suffering servant" as well as the faith of Abraham and the Passover. Porter explains that examining scriptural traditions is fundamental to understanding central ideas in the New Testament regarding Jesus. He sheds light on major themes in New Testament Christology and soteriology, offering fresh, constructive proposals.
Part 1. Background, method, and terminology : -- 1. Background to discussion of sacred tradition -- 2. Method and terminology in discussion of sacred tradition -- Part 2. Jesus and sacred tradition : -- 3. Daniel 7:13 and the Son of Man -- 4. Isaiah 42-53 and the suffering servant -- 5. The Son of God and the Messiah and Jesus -- Part 3. The Gospels and sacred tradition : -- 6. Exodus 12 and the Passover theme in John -- 7. Psalm 22 and the Passion of Jesus -- Part 4. The Epistles and sacred tradition : -- 8. Genesis 15:6 in Paul and James -- 9. Esau in Romans and Hebrew / Bryan R. Dyer -- 10. "Jesus Christ" in Paul's letters.
Includes bibliographical references (pages 251-286) and indexes.
Keywords: Bible. -- Relation to the Old Testament; Bible. -- Criticism, interpretation, etc; Christianity and other religions -- Early church, ca. 30-600.; Jesus Christ -- Person and offices